The 18th Romanian Textiles and Leather Conference : CORTEP 2022 - Rodica Harpa; Cristina Piroi; Adrian Buhu; Luminița Ciobanu (Sciendo, 2023)
The Romanian Textiles and Leather Conference CORTEP 2022 is a major international scientific event organized in Romania by the Faculty of Industrial Design and Business Management of the “Gheorghe Asachi” Technical University of Iasi. Now in its 18th edition, the Conference provides a platform for professionals and managers from the textiles, clothing, leather and footwear (TCLF) sector to exchange knowledge, new ideas and experiences, and gain an insight into the state-of-the-art in the current developments, solutions and research results. The 19th Romanian Textiles and Leather Conference The CORTEP events started in 1960 with a view to transforming our decades of experience in academic education and scientific research in the fields of textile and garment technologies, fashion design and industrial management. The further editions evolved into a successful and traditional conference. The conference is addressed to a large variety of stakeholders, from those interested in research and academia to specialists and managers from TCLF and other industrial sectors, professional associations and government organizations. This wide range of participants provides opportunities for fruitful exchange of new ideas and experiences, networking and development of research and/or business relations, as well as possible partners for future collaborations. With each edition, the conference is adapted to meet the needs of our community and industry. Topics for the 18th CORTEP International Conference include: New fibres and advanced materials; Textile science and technology; Innovative textile structures and processing; Smart textiles; Sustainable and functional textiles and clothing; Machinery developments; Fashion design and product development; Innovations in textile finishing; Advancements in leather processing; Footwear design and technology; Ecology in textiles and leather processing; New business models and emergent ecosystems; Entrepreneurship and innovation; Engineering education. Submission of articles via the Editorial Manager: https://www.editorialmanager.com/cortep/default2.aspxInformation about the conference: https://www.cortep.tuiasi.ro/ Organizing Committee Adrian BUHU, Gheorghe Asachi Technical University of Iasi, Iasi, Romania Liliana BUHU, Gheorghe Asachi Technical University of Iasi, Iasi, Romania Adriana BUJOR, Gheorghe Asachi Technical University of Iasi, Iasi, Romania Luminița CIOBANU, Gheorghe Asachi Technical University of Iasi, Iasi, Romania Angela DĂNILĂ, Gheorghe Asachi Technical University of Iasi, Iasi, Romania Ionuţ DULGHERIU, Gheorghe Asachi Technical University of Iasi, Iasi, Romania Rodica HARPA, Gheorghe Asachi Technical University of Iasi, Iasi, Romania Liliana HRISTIAN, Gheorghe Asachi Technical University of Iasi, Iasi, Romania Dorin IONESI, Gheorghe Asachi Technical University of Iasi, Iasi, Romania Raluca LAZARESCU, Gheorghe Asachi Technical University of Iasi, Iasi, Romania Daniela NEGRU, Gheorghe Asachi Technical University of Iasi, Iasi, Romania Marius PÎSLARU, Gheorghe Asachi Technical University of Iasi, Iasi, Romania Vasilica POPESCU, Gheorghe Asachi Technical University of Iasi, Iasi, Romania Cristina PIROI, Gheorghe Asachi Technical University of Iasi, Iasi, Romania Irina IONESCU, Gheorghe Asachi Technical University of Iasi, Iasi, Romania Alina IOVAN DRAGOMIR, Gheorghe Asachi Technical University of Iasi, Iasi, Romania Scientific Committee Pascal BRUNIAUX, École Nationale Supérieure Des Arts Et Industries Textiles, Rou